An update on the current status and prospects of nitrosation pathways and possible root causes of nitrosamine formation in various pharmaceuticals - Wisut Wichitnithad; Siriwan Nantaphol; Kachathong Noppakhunsomboon; Pornchai Rojsitthisak (Elsevier, 2023)
Over the last two years, global regulatory authorities have raised safety concerns on nitrosamine contamination in several drug classes, including angiotensin II receptor antagonists, histamine-2 receptor antagonists, antimicrobial agents, and antidiabetic drugs. To avoid carcinogenic and mutagenic effects in patients relying on these medications, authorities have established specific guidelines in risk assessment scenarios and proposed control limits for nitrosamine impurities in pharmaceuticals. In this review, nitrosation pathways and possible root causes of nitrosamine formation in pharmaceuticals are discussed. The control limits of nitrosamine impurities in pharmaceuticals proposed by national regulatory authorities are presented. Additionally, a practical and science-based strategy for implementing the well-established control limits is notably reviewed in terms of an alternative approach for drug product N-nitrosamines without published AI information from animal carcinogenicity testing. Finally, a novel risk evaluation strategy for predicting and investigating the possible nitrosation of amine precursors and amine pharmaceuticals as powerful prevention of nitrosamine contamination is addressed.